Graph Theoretical Approaches To Solving Combinatorial Optimization Problems - Bijumon Ramalayathil; Aneesh Kumar K (Revista Electronica de Veterinaria, 2024)
Combinatorial optimization problems play a crucial role in various fields such as logistics, network design, scheduling, and bioinformatics. Graph theory provides a structured approach to model and solve these problems efficiently. This paper explores key graph theoretical techniques for solving combinatorial optimization problems, including shortest path algorithms, maximum flow, minimum spanning tree, and graph coloring. We discuss their mathematical formulations, computational complexity, and real-world applications, emphasizing algorithmic strategies like Dijkstra’s algorithm, the Ford-Fulkerson method, and the Prim-Kruskal approach.